Discovering the Views of Indonesian Students’ Responses to Use the Booklet During the Covid-19 Pandemic Situation - Ruqiah Ganda Putri Panjaitan*; Galih Albarra Shidiq; Titin Titin; Eko Sri Wahyuni (Universitas Syiah Kuala, 2021)
The Covid-19 situations impacted the teaching and learning which reducing our activities by using the online platforms. The booklet is one of the solutions to use during a covid-19 situation which provides the opportunity to improve the learning process. This study aims to discover students’ responses to use the booklet as learning media which contains the results of an inventory of medicinal plants in the biology courses. The questionnaire sheet was used as the instrument which contains the affective, cognitive, and conative aspects of students, and the questionnaire has 11 statement items. The participants of this study consist of 34 students. The results showed the average percentage of responses in each aspect were 77.59; 81.32; 83.19 to respectively the affective, cognitive, and conative aspects. It can be concluded that the developed booklet media received a positive response from students. However, in this paper, students’ responses using the booklet practices are described, as well as the reflections of their learning activities